Alkali metal sulfate: A new non-π-conjugated deep-ultraviolet quasi-phase matching crystal. (August 2022) - Sha, Hongyuan; Xu, Junxin; Huang, Lingxiong; Xiong, Zheyao; Wang, Zujian; Su, Rongbing; He, Chao; Yang, Xiaoming; Long, Xifa
Abstract: Nonlinear optical crystals with ferroelectricity could realize frequency conversion based on the quasi-phase matching principal, which could effectively break the limitation of the inherent birefringence. Here, an alkali metal sulfate crystal, LiKSO4, is found, which combines a short absorption cutoff edge of 160 nm, a large second harmonic generation response of 4 × KH2 PO4 and the typical ferroelectric polarization reversal into a single structure. Besides, it possesses an optimized Sr2 Be2 B2 O7 -like structure with -S-O-Li- bonds in the adjacent layers, which effectively avoids the layer growth tendency. Therefore, this manuscript provides the first sulfate deep-ultraviolet quasi-phase matching crystal, which opens a new horizon for the development of deep-ultraviolet nonlinear optical materials. Graphical abstract: Image, graphical abstract